2020
DOI: 10.1088/1742-6596/1500/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Wear on Artificial Hip Joint with Dimple on Femoral Surface

Abstract: This paper proposes the replacement of artificial hip joints which is one of the successful methods used to restore the movement of damaged hip bones. The main contribution of this work is to reduce wear caused by contact pressure between the femoral head and acetabular cup surfaces, where the average wear rate is very high. This can be achieved through the use of dimple on the femoral head surface from the artificial hip joint and subsequently computed by using the Archard equation. To validate the contact pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Because the weight of an adult person, which is determined by selecting the face area that is displayed in Figure 8a, is very close to the define weight at the femur head in the downward direction, we estimate that the maximum gait load in the current situation is 2000 N, and it acts in the downward z-direction. This conclusion is based on the information that is discussed in Ramadhoni et al (2020), and it acts in the downward z-direction.…”
Section: Fig 7 Meshing Geometrymentioning
confidence: 94%
“…Because the weight of an adult person, which is determined by selecting the face area that is displayed in Figure 8a, is very close to the define weight at the femur head in the downward direction, we estimate that the maximum gait load in the current situation is 2000 N, and it acts in the downward z-direction. This conclusion is based on the information that is discussed in Ramadhoni et al (2020), and it acts in the downward z-direction.…”
Section: Fig 7 Meshing Geometrymentioning
confidence: 94%
“…Archard's wear equation was then extensively used to calculate the wear on the liner surface of the hip prosthesis by many studies. 4951 Also, an alternative well-known method for calculating wear according to Archard's law in a hip prosthesis was introduced by Pakhaliuk et al 52,53…”
Section: Methodsmentioning
confidence: 99%
“…Archard's wear equation was then extensively used to calculate the wear on the liner surface of the hip prosthesis by many studies. [49][50][51] Also, an alternative well-known method for calculating wear according to Archard's law in a hip prosthesis was introduced by Pakhaliuk et al 52,53 After a century of debate, it seems unlikely that a single governing equation will be created to account for all aspects of wear theory. For a wide variety of situations, however, both adhesive and abrasive, it has been shown that the wear volume W v (mm 3 ), load L (N), and sliding distance S L (m) are connected by an equation of the form:…”
Section: Wearmentioning
confidence: 99%
“…Minimizing the wear that occurs on metal to metal is essential to reduce the risk of adverse toxic side effects. So far, previous research has only aimed at optimization of THA implants, including optimization topology, geometric dimensions and addition of dimples Ramadhoni et al, 2020; with the aim of increasing hydrodynamic pressure and increasing the thickness of the lubrication film and material modification to minimize wear. Even though there are internal factors that can have an effect on poor results, namely body mass index towards obesity which results in an increase in complications of failure after THA implantation surgery.…”
Section: Introductionmentioning
confidence: 99%